Prevalence of risk factors for noncommunicable diseases among adult population in an urban slum of Pune, India - Anshuman Ghildiyal; Rajneesh Kumar Joshi; Sanjay Kumar Dutt; Vishwavijet Mopagar; Ananta Kumar Naik (Medical Journal of Dr. D.Y. Patil Vidyapeeth, 2022)
Introduction: India is experiencing health transition with a rising burden of noncommunicable diseases (NCDs). There is a need to study risk factors of NCDs among poor and underprivileged section of the society. Methodology: A cross-sectional study was done among adults in an urban slum in Pune using the World Health Organization's STEP wise approach to surveillance (STEPS). Two hundred individuals selected by simple random sampling participated in this study. Information regarding dietary habits, physical activity, and tobacco and alcohol consumption was obtained. Physical measurements of height, weight, waist and hip circumference, and blood pressure were also done. Nominal and numerical variables in different groups were compared by Fisher's exact test and Student's t-test, respectively. Logistic regression was used to determine the association of various factors with high blood pressure. Results: Tobacco and alcohol consumption was observed in 22.5% (95% confidence interval [CI]: 16.9%–28.9%) and 11.5% (95% CI: 7.4%–16.8%) of individuals, which was significantly higher among males. 40.0% (95% CI: 33.2%–47.1%) of participants were doing less than recommended physical activity. 47% (95% CI: 40.0%–54.2%) of individuals were overweight or obese. The prevalence of high blood pressure was found to be 43.9% (95% CI: 36.6%–51.3%). Significant positive correlation was observed among different anthropometric variables. Multivariable logistic regression showed that there was significant positive association of high blood pressure with age (adjusted odds ratio [aOR] = 1.05 [95% CI: 1.02–1.08]) and waist hip ratio (aOR = 1.45 [95% CI: 1.01–2.09]). Conclusions: There is a high prevalence of risk factors for NCDs among residents of urban slum. Behavior change communication is required for adoption of healthy lifestyle and prevents NCDs in urban slums.